Rocking curves of gold nitride species prepared by arc pulsed - physical assisted plasma vapor deposition (2017)
Gold nitride is important for potential applications, such as, to replace metallic gold in electronics, coatings, jewelry and micro-engineering. However, the experimental determination of crystalline structure is still controversial due to difficulties in the synthesis (it is difficult to obtain a sufficient amount). In this work gold nitride species are obtained at the 304 stainless steel substrates by using an arc pulsed - physical assisted plasma vapor deposition system. The pressure of nitrogen at the discharge time was varied between 3.5 at 8.0 mbar to increase the amount of gold nitride species in the sample. By X-ray diffraction, changes in the texture coefficient of (111) to (200) planes are observed, and increase of the micro strain, asymmetries and widening of the rocking curves shown. By the X-ray photoemission spectroscopy, the N 1s core levels observed at binding energies of 398.1 eV and 398.3 eV, are attributed to formation of gold nitride species. The rocking curves of gold nitride films are modeled by using a recent theory of shape and influential curves. From this modelling, a cubic crystalline structure of the gold nitride is proposed. © 2016 Elsevier B.V.